Disparitas Pidana pada Putusan Pengadilan Terhadap Pertanggungjawaban Pelaku Tindak Pidana Penggelapan - Delta, Ria; Melati, Dwi Putri; Aryata, I Nengah (Universitas Sang Bumi Ruwa Jurai, 2024)
Discussion of criminal acts in community life is often a very interesting study, especially related to the disparity in criminal decisions handed down. The problem in this study is how is the responsibility of the perpetrators of embezzlement based on Decision Number 452 / Pid.B / 2023 / PN.Tjk, Decision Number 745 / Pid.B / 2022 / PN.Tjk and Decision Number 807 / Pid.B / 2022 / PN.Tjk? and how is the disparity in criminal sentences in court decisions regarding the responsibility of perpetrators of embezzlement based on Decision Number 452 / Pid.B / 2023 / PN.Tjk, Decision Number 745 / Pid.B / 2022 / PN.Tjk and Decision Number 807 / Pid.B / 2022 / PN.Tjk? The problem approach used in this study consists of a normative legal approach and an empirical legal approach. The types of data used are primary data and secondary data. Data analysis was carried out using a qualitative descriptive method. The disparity in criminal sentences in court decisions regarding the responsibility of perpetrators of embezzlement based on Decision Number 452/Pid.B/2023/PN.Tjk, Decision Number 745/Pid.B/2022/PN.Tjk and Decision Number 807/Pid.B/2022/PN.Tjk there was injustice in the verdicts imposed because the Articles and levels of losses incurred by the defendant were not the same, and the sentences imposed were different and would give rise to various perceptions in society about justice itself